2021
DOI: 10.3389/fpsyt.2021.638651
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Alzheimer's Disease: A Delphi Consensus on Etiology, Risk Factors, and Clinical Management

Abstract: Background: Alzheimer's disease (AD) and other forms of dementia are among the most common causes of disability in the elderly. Dementia is often accompanied by depression, but specific diagnostic criteria and treatment approaches are still lacking. This study aimed to gather expert opinions on dementia and depressed patient management to reduce heterogeneity in everyday practice.Methods: Prospective, multicenter, 2-round Modified Delphi survey with 53 questions regarding risk factors (11), signs and symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 97 publications
(139 reference statements)
0
39
0
4
Order By: Relevance
“…Indeed, depression in elderly patients can also be considered a sign or a risk factor for the development of dementia, requiring a careful assessment of the patient condition, since the diagnosis of these diseases is very challenging. In early AD, depression symptoms generally translate into a sadder mood and depressive thoughts, while in more advanced states, problems with agitation, aggression and circadian rhythm alterations are more evident [ 5 ]. Another important finding is the fact that about a third of adults who have depression are also diagnosed with mild cognitive impairment (MCI), which precedes severe forms of AD [ 30 ].…”
Section: Alzheimer’s Disease and Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, depression in elderly patients can also be considered a sign or a risk factor for the development of dementia, requiring a careful assessment of the patient condition, since the diagnosis of these diseases is very challenging. In early AD, depression symptoms generally translate into a sadder mood and depressive thoughts, while in more advanced states, problems with agitation, aggression and circadian rhythm alterations are more evident [ 5 ]. Another important finding is the fact that about a third of adults who have depression are also diagnosed with mild cognitive impairment (MCI), which precedes severe forms of AD [ 30 ].…”
Section: Alzheimer’s Disease and Depressionmentioning
confidence: 99%
“…Once again, mirtazapine was not effective in the treatment of sleep disorders (regarding the duration and quality of nighttime sleep), increasing the daytime sleepiness [ 117 ]. Moreover, another recent investigation (based on the collection of opinions from experts in the field) demonstrated that in patients with AD and depression, one of the antidepressants of choice is mirtazapine, characterized by having a dual mechanism of action and by leading to improvements in cognitive function/depressive episodes [ 5 ]. Furthermore, a systematic review and network meta-analysis concluded that sertraline and mirtazapine improved depressive symptoms, with no differences in cognitive function.…”
Section: Mirtazapinementioning
confidence: 99%
See 2 more Smart Citations
“…Alzheimer’s disease is also accompanied by neuropsychiatric symptoms, including depression [ 68 ]. According to the meta-analysis of recent studies, up to 16% of AD patients exhibited major depression [ 69 ]. AD increases the severity of depression, which in turn induces cognitive impairments [ 70 ].…”
Section: Shared Symptoms Of Asd and Admentioning
confidence: 99%